Multilayered MoS2/C nanospheres as high performance additives to lubricating oils - Kotsyubynsky, V.; Shyyko, L.; Shihab, Th.; Prysyazhnyuk, P.; Aulin, V.; Boichuk, V.; Коцюбинський, В. О.; Шийко, Л. О.; Шіхаб, Т. А.; Присяжнюк, П. М.; Аулін, В. В.; Бойчук, В. М. (Elsevier Ltd, 2021)
The main goal of the present work was the investigation of tribological properties of multilayered hydrothermally synthesized MoS2/C nanospheres as an additive to industrial base oil. The average size of the MoS2/C particles in which MoS2 layers alternate with carbon is about 40 nm. The tests were performed for reciprocating motion conditions through ‘‘plane-ball” scheme. The main tribological characteristics (critical point of failure and friction coefficient) changes as functions of the lubricant additives concentration were discussed. The time dependencies of the tribological characteristic were fitted by sigmoid functions. It was found that the addition of 0.1 wt% MoS2/C nanoparticles to the base oils results in 30% up in friction coefficient reduction and 10 times enlarging of critical point of failure. Головною метою даної роботи було дослідження трибологічних властивостей багатошарових гідротермічно синтезованих наносфер MoS2 / C як добавки до промислової базової олії. Середній розмір частинок MoS2 / C, у яких шари MoS2 чергуються з вуглецем, становить близько 40 нм. Випробування проводились для зворотно-поступальних рухів за схемою «площина-куля». Обговорювались основні трибологічні характеристики (критична точка руйнування та коефіцієнт тертя) як функції концентрації мастильних добавок. Часові залежності трибологічної характеристики відповідали сигмовидним функціям. Було виявлено, що додавання 0,1 мас.% Наночастинок MoS2 / C до базових масел призводить до 30% збільшення коефіцієнта тертя та 10-кратного збільшення критичної точки руйнування.
Багатошарові наносфери MoS2 / C як високоефективні добавки до олив
Keywords: MoS2; carbon; nanospheres; composite; critical point of failure; MoS2; вуглець; наносфери; композит; критична точка відмови